Morphometric relations of fractal-skeletal based channel network model - B. S. Daya Sagar; Charles Omoregie; B. S. Prakasa Rao (Discrete Dynamics in Nature and Society, 1998)
A fractal-skeletal based channel network (F-SCN) model is proposed. Four regular sided initiator-basins are transformed as second order fractal basins by following a specific generating mechanism with non-random rule. The morphological skeletons, hereafter referred to as channel networks, are extracted from these fractal basins. The morphometric and fractal relationships of these F-SCNs are shown. The fractal dimensions of these fractal basins, channel networks, and main channel lengths (computed through box counting method) are compared with those of estimated length–area measures. Certain morphometric order ratios to show fractal relations are also highlighted.